Democracy in Kingston: A Social Movement in Urban Politics, 1965-70 - McBride, Joy (Labour / Le Travail, 1991)
The article reviews the book, "Democracy in Kingston: A Social Movement in Urban Politics 1965-1970," by Richard Harris.
Keywords: BOOKS – Reviews; DEMOCRACY in Kingston: A Social Movement in Urban Politics 1965-1970 (Book); HARRIS; Richard; Nonfiction; Social movements